2014
DOI: 10.1042/bst20130133
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic molecular effects of theMycobacterium ulceransvirulence factor mycolactone underlying the cell death and immunosuppression seen in Buruli ulcer

Abstract: Mycolactone is a polyketide macrolide lipid-like secondary metabolite synthesised by Mycobacterium ulcerans, the causative agent of Buruli ulcer (BU), and is the only virulence factor for this pathogen identified to date. Prolonged exposure to high concentrations of mycolactone is cytotoxic to diverse mammalian cells (albeit with varying efficiency), whereas at lower doses it has a spectrum of immunosuppressive activities. Combined, these pleiotropic properties have a powerful influence on local and systemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 54 publications
1
52
0
Order By: Relevance
“…Notably, most of the type I TMPs that are mycolactone-sensitive at a cellular level have N-terminal domains of a similar or larger size (cf. Hall and Simmonds, 2014), including thrombomodulin, consistent with the previously suggested mycolactone-dependent inhibition of its ER translocation (Ogbechi et al, 2015). Our limited in vitro analysis of type II TMPs suggests that their membrane integration is highly sensitive to mycolactone, and this is consistent with previous observations using TNFα (Hall et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Notably, most of the type I TMPs that are mycolactone-sensitive at a cellular level have N-terminal domains of a similar or larger size (cf. Hall and Simmonds, 2014), including thrombomodulin, consistent with the previously suggested mycolactone-dependent inhibition of its ER translocation (Ogbechi et al, 2015). Our limited in vitro analysis of type II TMPs suggests that their membrane integration is highly sensitive to mycolactone, and this is consistent with previous observations using TNFα (Hall et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Both secreted mediators, such as cytokines and chemokines, as well as TMPs, such as receptors, are under-produced in cells treated with mycolactone, while cytoplasmic substrates appear to be consistently unaffected (Coutanceau et al, 2007; Hall and Simmonds, 2014; Simmonds et al, 2009). Our current study suggests that type I TMPs with N-terminal domains of more than ∼100 residues are highly sensitive to mycolactone treatment in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The intricacies of translation and its control in disease states means that, even when translational control is implicated in disease progression, the mode of such control can be elusive. Hall and Simmonds [23] expertly summarize our knowledge of mycolactone action on mammalian cells. This polyketide lactone is produced by Mycobacterium ulcerans, the causative agent of Buruli ulcer, a severe disease characterized by the development of chronic necrotizing skin ulcers at the sites of infection.…”
Section: Translational Control: Dysregulation and Diseasementioning
confidence: 99%
“…45,46 Recent evidence has revealed that mycolactone exerts a profound effect on protein secretion by blocking the co-translational translocation of a plethora of proteins that pass through the endoplasmic reticulum for secretion or placement in cell membranes. 47,48 It is noteworthy that many of these proteins are important in wound healing, and we hypothesize that the rate of healing of ulcers under antibiotic treatment may be significantly impacted by the rate of clearance of mycolactone from tissues. Studies are underway to evaluate the synergy between tissue levels of mycolactone, bacterial load, and rate of wound healing in BUD in humans.…”
Section: Diagnostic Confirmationmentioning
confidence: 99%